Building an Integrated Service Management Platform for Ubiquitous Cities. - Jungwoo Lee; Songhoon Baik; Choonhwa Lee (Computer (00189162), 2011)
As one of the frontrunners in the race to build smarter cities, South Korea is pushing the envelope by promoting the development of a standard architecture for a service management platform that integrates ubiquitous computing and green technologies.